PENYUSUNAN RENCANA PENYEDIAAN ENERGI DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA DENGAN DUKUNGAN ENERGI TERBARUKAN - , Yusnan Badruzzaman, Dr. Sarjiya ST, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Yogyakarta does not have any non-renewable energy sources such as liquid fossil fuels, coal and natural gas. Consequently, these energy resources must be supplied from other provinces. The electricity system in Yogyakarta province is part of the electrical power interconnection system of Madura Jawa Bali (JAMALI). The potential of renewable energy are water, wind, solar, biomass and biofuels. This study aim to evaluated the existing and forcasting energy demand and supply in yogyakarta with renewable energy empowers to meet the target of the energy mix and energy elasticity to less than 1. Target energy mix for renewable energy based on scenario of KEN and KED are 17% and 9.28% in 2025. This study used a model of the LEAP (Long-range Energy Alternatives Planning System) version: 2011.0.0.40. This study uses three scenarios BAU, KEN and KED for the next of seventeen years with 2008 as base year and ended in 2025. The results of DIY energy demand by using KED scenario was found that the highest energy user sector is the transportation sector and the household sector. To be able to meet the target the elasticity ratio of energy carried out first by lowering the energy consumption in transport and electricity sectors. Transportation sector energy use by 53.49%, but provide added value to GDP is relatively small in the amount of 10.69%. Utility sector (electricity, water and gas) with the percentage of energy consumption by 36.41% to the value added to GDP is 0.91%. The second step is to increase economic growth in the commercial sector and agriculture. Commercial sector is the sector highest contributor to GDP at 23.90% with the first use of energy is only 4.25%. The agricultural sector can provide added value by 18.59% of GDP and energy consumption is only 0.50%. With existing resources, renewable energy generation in 2011 accounted for only 0.88% of total load. In 2025 the renewable energy generation is expected to contribute to the energy mix by 5%. with the following composition solar power plant 45.04%, Micro hydro power plant 11.26%, Wind power plant 2.4% and 41.30% Biomass.